Negative governmentality through fundamental rights: the far side of the European Convention on Human Rights - Nasir, Muhammad Ali (European law journal, 2018)
This essay analyses those statements that mention legal norms in negative terms. Specifically, it analyses those statements that define a legal system by mentioning how legal protection does not work and where legal protection ends, and those statements that identify what rights-holders do not have to with their legally protected free capacities. This essay argues that these statements address a systemic question. It calls such a dynamic as negative governmentality. The argument proceeds in four steps. It introduces the concept of negative governmentality by arguing that the idea of freedom requires both the positive affirmation of moral agency and the constraining of moral agency (Section 2). It then explores how rights constitute freedom by limiting rights or making exceptions to them (Section 3). Later, it analyses how rights-based norms prevent abuse of rights by holders of rights (Section 4). Finally, it sees how rights-based norms constrain the legal guarantor of rights, i.e., a state (Section 5). The essay concludes by mentioning the importance of negative governmentality (Section 6).
Gesehen am 11.12.2019
Keywords: Beschränkung; Rechtssystem; Convention for the Protection of Human Rights and Fundamental Freedoms (1950-11-04)